The Formation of Philologocentric Culture Approaching the Principle of Global Axiology: From Special Theory and Methodology to the General Theory and Methodology of Creativity - Botezatu, Liuba (Advances in Social Sciences Research Journal, 2022)
The formation of philologocentric culture in the alternation of "multiple intelligences"/ J.P. Guilford - "multiple graces"/ L.Botezatu is mobilized in the entire content of the present to demonstrate the effectiveness of the integrationist- associationist correlation: Theory and Special Methodology of Creativity - General Theory and Methodology of Creativity to the revalorization of the evolutionary-self- evaluative potential, opposite the Methodology of Formative Potentials Vehicle "6 to 6" (Annex 3) - Methodology of Evidence of Axiological Completions (Annex 4). Thus, at the head of the table of preoccupational efforts, there is an ever more insistent place: a) that "plan to guide education"/J.Dewey; b) a principle of complete divination, opposite the 10 theories of cutting-edge creativity (Appendices 1 and 2); c) I.Druță "pastoral staff"/ the authenticating spirit connected to the "sovereign inner principle"/M.Cimpoi; c) The uniqueness of A.Einstein’s wisdom: "Science without religion is lame, religion without science is blind"; d) The Principle of Global Axiology - the backbone of the entire human race.